2017
DOI: 10.19071/cb.2017.v8.3231
|View full text |Cite
|
Sign up to set email alerts
|

Adventitious root formation in branch cuttings of Taxus wallichiana Zucc.(Himalayan yew): A clonal approach to conserve the scarce resource

Abstract: Himalayan yew (<em>Taxus wallichiana</em> Zucc.), is an economically valuable plant and critically endangered due to overexploitation for the isolation of Taxol,an exciting anticancer drug from its bark and leaves. Since the species is unisexual and due to its long seed dormancy period and rapid loss of viability coupled with low survival percentage, its natural regeneration from seeds is very poor. As the seed raised plants add little growth, propagation by stem cuttings was tried under natural co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Another study reported regeneration of T. wallichiana plant via shoot organogenesis from callus cultures derived from zygotic embryos (120). Apart from tissue culture techniques, stem cuttings treated with growth promoting substances have also been proved effective for propagation of the plant (121). Another recent study reported that treatment of shoot cuttings of the plant with indole acetic acid (IAA), indole butyric acid (IBA) and napthoxy acetic acid (NAA) resulted in effective initiation of roots (122).…”
Section: Conservational Approaches and Production Of Bioactive Compoundsmentioning
confidence: 99%
“…Another study reported regeneration of T. wallichiana plant via shoot organogenesis from callus cultures derived from zygotic embryos (120). Apart from tissue culture techniques, stem cuttings treated with growth promoting substances have also been proved effective for propagation of the plant (121). Another recent study reported that treatment of shoot cuttings of the plant with indole acetic acid (IAA), indole butyric acid (IBA) and napthoxy acetic acid (NAA) resulted in effective initiation of roots (122).…”
Section: Conservational Approaches and Production Of Bioactive Compoundsmentioning
confidence: 99%
“…It is a dioecious, evergreen tree found in the temperate Himalayas at altitudes between 1800 and 3300 m [2]. It is a slow‐growing, medium‐sized conifer that attains a height of about 30 m. It has horizontal branches and leaves are flat, dark green, and arranged spirally on the stem [3]. It has high medicinal value and ethnobotanical importance [4].…”
Section: Introductionmentioning
confidence: 99%